Organizational Justice as an Antecedent of Job Performance - Nasurdin, Aizzat Mohd.; Khuan, Soon Lay (Gadjah Mada International Journal of Business, 2007)
The present research examines the influence of organizational justice (distributive justice and procedural justice) on predicting job performance (task performance and contextual performance). Survey data were drawn from a sample of 136 customer-contact employees within the telecommunications industry in Malaysia. Results of the regression analysis illustrate that distributive justice alone has a significant and positive relationship with task performance. On the other hand, only procedural justice is found to be significantly and positively related to contextual performance. Implications of the findings and directions for future research are highlighted.